Jaghrāfiyā-yi Ḥāfiẓ-i Abrū. Volume 2 : Mushtamil bar jaghrāfiyā-yi tārīkhi-yi Midītirana, Armanistān, Firingistān, Jazīra, ʿIrāq, Khūzistān wa Fārs - Abrū, Ḥāfiẓ, (Miras Maktoob, ISBN: 9789004365452., 2019)
Ḥāfiẓ Abrū (d. 833/1430) was a Timurid historian who spent the greater part of his active life in Herat. An accomplished chess-player, he was a regular guest at the court of the chess-loving Tīmūr Lang (d. 807/1405). His works were all commissioned by Tīmūr's son Shāhrūkh (d. 850/1447), whom he had joined at his court in Herat after his accession to the throne in 807/1405. The Jaghrāfiyā is of special interest because in the parts on Fārs, Kirmān,Transoxania and Khurāsān, geographical data-often collected personally by him during military campaigns in which he took part-are supplemented with much valuable historical information. The three volumes published here contain the first of the two books of which the Jaghrāfiyā is composed, treating of Kirmān (vol. 3), Fārs (vol. 2), and the known world to the west of these (including Arabia), with separate listings of mountains, rivers, lakes and seas (vol.1 , beginning vol. 2). 3 vols; volume 2.